Error analysis in Croatian morphosyntactic tagging - Agić, Željko; Tadić, Marko; Dovedan Han, Zdravko (2009)
In this paper, we provide detailed insight on properties of errors generated by a stochastic morphosyntactic tagger assigning Multext-East morphosyntactic descriptions to Croatian texts. Tagging the Croatia Weekly newspaper corpus by the CroTag tagger in stochastic mode revealed that approximately 85 percent of all tagging errors occur on nouns, adjectives, pronouns and verbs. Moreover, approximately 50 percent of these are shown to be incorrect assignments of case values. We provide various other distributional properties of errors in assigning morphosyntactic descriptions for these and other parts of speech. On the basis of these properties, we propose rule- based and stochastic strategies which could be integrated in the tagging module, creating a hybrid procedure in order to raise overall tagging accuracy for Croatian.
Projekt MZOS
Projekt MZOS
ENG